Judicial branch independence versus judicial branch control - (:unkn) unknown (My University, 2016)
In this article the author maintains that transferring responsibilities to the judicial branch without ensuring the appropriate balance of power may lead to closed and self-absorbed judicial systems, granting more power to the system than to the judges, and barely providing benefits for those who seek justice. He proposes that the transfer of powers or the process of endowing judicial systems with greater independence goes hand-in-hand with measures that allow for making the judicial systems more open to public scrutiny. More concretely, he proposes policies to decentralize and “flatten” the judicial organization in order to better define its functions and make its work more public. Finally, he affirms the advantages of maintaining the sector’s policies in the hands of those who directly retain the popular sovereignty, without jeopardizing the participatory spaces that should be built into their design or hindering the performance of the members of the judicial system.